A review of game theory applications for seaport cooperation and competition - Pujats, Karlis; Golias, Mihalis; Konur, Dinçer (My University, 2020)
In the ever-changing maritime shipping industry, ports, and more specifically, container terminals, are always on the search for better policy and operational plan developments. As the maritime shipping sector changes, new areas of research emerge. In this paper, we present a review of recent game theory applications for seaport cooperation and competition, accompanied by summary review tables stating the study, the modeling technique used, the methodology and objective, and summary of the results of each study. In total, we have reviewed 33 studies that used game theory models that investigated seaport and container terminal competition and cooperation involving various stakeholders with dating publication years from 2008 to 2019. The paper concludes with a discussion and proposed future research directions. The purpose of the paper is to serve as a reference guide to recent game theory applications on seaport cooperation and competition that would allow a quick understanding of work done in the field.
Keywords: competition; cooperation; seaports; container terminals; game theory